Prevalence of Tubal Factor Infertility Clinical Insight and Diagnostic Approaches - Shafia Afridi, Asma Ambareen, Shagufta Naz (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To assess the prevalence of tubal factor infertility, compare diagnostic methods, and explore associations with demographic and clinical factors. Methodology: A total of 200 women diagnosed with infertility were included in this retrospective study. The diagnostic methods used were Hysterosalpingography (HSG), diagnostic laparoscopy, and sonosalpingography (SSG). Descriptive statistics were used to summarise patient characteristics, and Chi-square tests were applied to evaluate associations between diagnostic methods and tubal status. Statistical significance was set at p < 0.05. Results: The study found that 50% of the patients had blocked tubes, 30% had patent tubes, and 20% had hydrosalpinx. No significant difference in diagnostic outcomes was observed between HSG, laparoscopy, and SSG (p = 0.49). Age and comorbidities such as diabetes and hypertension did not significantly correlate with tubal status (p = 0.93). These findings suggest that tubal occlusion is the most common cause of infertility in this cohort, and diagnostic methods did not significantly impact the outcome. Conclusion: The study highlights that tubal factor infertility remains a prevalent cause of infertility. Sonosalpingography presents a promising non-invasive alternative to traditional methods like HSG and laparoscopy. The study calls for larger, multicenter prospective studies to validate these findings and optimise diagnostic approaches for tubal factor infertility in resource-limited settings. Keywords: tubal factor infertility, diagnostic laparoscopy, hysterosalpingography, sonosalpingography, infertility diagnostics.